Paired associative stimulation applied to the cortex can increase resting-state functional connectivity: A proof of principle study. (27th July 2022) - Hooyman, Andrew; Garbin, Alexander; Fisher, Beth E.; Kutch, Jason J.; Winstein, Carolee J.
Highlights: Reliability of baseline resting-state coherence established levels of meaningful change in coherence due to paired associative stimulation. Meaningful increases to targeted resting-state functional connectivity are timing dependent. Seventy percent of participants experienced a significant increase in targeted coherence compared to a control condition. Abstract: Introduction: There is emerging evidence that high Beta coherence (hBc) between prefrontal and motor corticies, measured with resting-state electroencephalography (rs-EEG), can be an accurate predictor of motor skill learning and stroke recovery. However, it remains unknown whether and how intracortical connectivity may be influenced using neuromodulation. Therefore, a cortico–cortico PAS (ccPAS) paradigm may be used to increase resting-state intracortical connectivity (rs-IC) within a targeted neural circuit. Purpose: Our purpose is to demonstrate proof of principle that ccPAS can be used to increase rs-IC between a prefrontal and motor cortical region. Methods: Eleven non-disabled adults were recruited (mean age 26.4, sd 5.6, 5 female). Each participant underwent a double baseline measurement, followed by a real and control ccPAS condition, counter-balanced for order. Control and ccPAS conditions were performed over electrodes of the right prefrontal and motor cortex. Both ccPAS conditions were identical apart from the inter-stimulus interval (i.e ISI 5 ms: real ccPAS and 500 ms: control ccPAS). Whole brain rs-EEG of high Beta coherence (hBc) was acquired before and after each ccPAS condition and then analyzed for changes in rs-IC along the targeted circuit. Results: Compared to ccPAS500 and baseline, ccPAS5 induced a significant increase in rs-IC, measured as coherence between electrodes over right prefrontal and motor cortex, (p <.05). Conclusion: These findings demonstrate proof of principle that ccPAS with an STDP derived ISI, can effectively increase hBc along a targeted circuit.